Preparing Multifunctional Technical Textiles for Electromagnetic Shielding and Personal Protective Equipment Applications - Mohammadimofarah, Hamed (Université d'Ottawa / University of Ottawa, 2024)
At the author’s request, the abstract has been removed due to the confidential nature of the thesis. It will be added once the embargo period has passed. À la demande de l'auteur, le résumé a été retiré en raison de la nature confidentielle de la thèse. Il sera ajouté une fois la période d'embargo terminée.
Keywords: Electromagnetic Shielding Effectiveness (EMI SE); AgNPs; Reactive Coating; Antiviral; HCoV-229E; AgNRs; AgNCs; Hydrophobicity; Textile; MXene; Copper Filament; PPE